BAHASA PEMIKAT HATI PELANGGAN : KREATIVITAS BAHASA DALAM INDUSTRI KREATIF - Syahruddin Syahruddin; Risma Ruslan (Titik Dua: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
The Language of Captivating Customers' Hearts: Language Creativity in the Creative Industry. This study aims to: (1) describe the form of language in the creative industry of fashion products (2) describe the function of language in fashion products that use the customer's heart (3) describe consumer responsses to language that creates attractiveness. This type of research is qualitative research. Sources of data in this study are the fashion industry, and informants based on gender, age, and occupation. Data collection techniques were carried out by documentation, questionnaires, and interviews. The research instrument consisted of the main instrument being the researcher and the supporting instruments, namely voice recordings, and data analysis guides. The results of the study revealed that the forms of language used in T-shirt products were the use of regional languages, wise words, word games, proverbs, plays, rhymes, expressions, appeals, and funny words. The language functions in t-shirt fashion products are the entertaining function, the motivating function, and the inspiring function. In addition, consumer responsses can be seen on the three variables such as by gender, age, and occupation. Various forms of language use on t-shirts are due to different consumer choices/tastes, with various language functions that make consumers really believe in choosing these fashion products.